Group-based trajectories of maternal intake of sugar-sweetened beverage and offspring oral health from a prospective birth cohort study - Ha, D.H.; Nguyen, H.; Dao, A.; Golley, R.K.; Thomson, D.M.; Manton, D.J.; Leary, S.; Scott, Jane; Spencer, A.J.; Do, Loc (Elsevier, 2022)
Objectives: To investigate the trajectory of maternal intake of sugar-sweetened beverages (SSB) during the first five years of their child’s life and its effect on the child’s dental caries at five years-of-age.